2017
DOI: 10.1093/humrep/dex031
|View full text |Cite
|
Sign up to set email alerts
|

Euploidy rates in donor egg cycles significantly differ between fertility centers

Abstract: No external funds were used for this study. S. Munne is a founding principle of Reprogenetics/current employee of Cooper Genomics. M Alikani's spouse is a founding principle of Reprogenetics/current consultant for Cooper Genomics. The remaining authors have no conflicts to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 54 publications
2
59
2
Order By: Relevance
“…Moreover, other studies and reports, in which the patient cohort was made up of only oocyte donors, the pregnancy rate was around 50% [28,29]. Also, the aneuploidy rate could be around 25%, and, depending on the age of the sperm donor, exceed 60% [9, 10, 30]. Therefore, we believe that the oocyte donor group does represent the typical donor make‐up of Central Mexicans.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, other studies and reports, in which the patient cohort was made up of only oocyte donors, the pregnancy rate was around 50% [28,29]. Also, the aneuploidy rate could be around 25%, and, depending on the age of the sperm donor, exceed 60% [9, 10, 30]. Therefore, we believe that the oocyte donor group does represent the typical donor make‐up of Central Mexicans.…”
Section: Discussionmentioning
confidence: 84%
“…These hormones are shown to affect protein synthesis, cellular division, and membrane fluidity and structure—key factors associated with embryo implantation [8]. Moreover, the aneuploidy rate of donor oocyte derived embryos, which ranges between 20 and 60% [9], are similar to patient oocyte derived embryos, when the patient's age is above 27 years [10]. Interestingly, Munne and colleagues demonstrated that the euploidy rate is associated with IVF clinics, thus indicating the procedural, material, and professional experience and preferences lead to a clinic effect [9].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models, changes in oxygen tension during embryo culture have been shown to affect chromosomal mosaicism rates . Recently, the incidence of chromosome abnormalities in human embryos has been shown to be fertility center‐dependent, indicating that mosaicism rate could very probably be influenced by culture conditions as temperature, pH and media composition …”
Section: Weaknessesmentioning
confidence: 99%
“…29 Recently, the incidence of chromosome abnormalities in human embryos has been shown to be fertility center-dependent, indicating that mosaicism rate could very probably be influenced by culture conditions as temperature, pH and media composition. 30 Although embryonic mosaicism was initially observed 25 years ago, 31 the emerging attribution of embryos as mosaics are because of two phenomena. First, genetic technologies for detecting chromosomal copy number variations in embryos have evolved from FISH to CCS platforms that represent a superior method for the assessment of mosaicisms.…”
Section: Management Of Mosaicismsmentioning
confidence: 99%
“…Several studies have used this model obtaining high pregnancy rates and good obstetrical outcomes in recipients ( Sauer & Kavic, 2006 ; Budak et al ., 2007 ). Regarding chromosome abnormalities in embryos of egg donors, several studies reveal percentages of aneuploidy embryos to be between 39-82% ( Reis Soares et al ., 2003 ; Munné et al ., 2006 ; Sills et al ., 2014 ; García-Ferreyra et al ., 2015 ; Haddad et al ., 2015 ; Munné et al. , 2017 ), and only García-Ferreyra et al .…”
Section: Introductionmentioning
confidence: 97%